2024
DOI: 10.3390/vaccines12010071
|View full text |Cite
|
Sign up to set email alerts
|

DNA Vaccines: Their Formulations, Engineering and Delivery

Michael Kozak,
Jiafen Hu

Abstract: The concept of DNA vaccination was introduced in the early 1990s. Since then, advancements in the augmentation of the immunogenicity of DNA vaccines have brought this technology to the market, especially in veterinary medicine, to prevent many diseases. Along with the successful COVID mRNA vaccines, the first DNA vaccine for human use, the Indian ZyCovD vaccine against SARS-CoV-2, was approved in 2021. In the current review, we first give an overview of the DNA vaccine focusing on the science, including adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 204 publications
0
5
0
Order By: Relevance
“…This problem may be solved by the use of modern NFIS. An increase in the immunogenicity of a DNA vaccine administered using NFIS may be associated with a wider distribution of the injected drug within tissues and more efficient delivery into cells [11,14,31]. Moreover, the injection process can act as a physical adjuvant during vaccination [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem may be solved by the use of modern NFIS. An increase in the immunogenicity of a DNA vaccine administered using NFIS may be associated with a wider distribution of the injected drug within tissues and more efficient delivery into cells [11,14,31]. Moreover, the injection process can act as a physical adjuvant during vaccination [56].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines based on nucleic acids do not cause an unwanted anti-vector immune response, which is typical for vaccines based on viral vectors and, therefore, can be administered repeatedly. DNA vaccines are also stable over a wide temperature range [10,11]. So, vaccines based on nucleic acids can be considered as a platform technology that makes it quite easy to replace the target immunogen, without the need to change production [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, Martinon et al demonstrated that administration of mice with a mixture of mRNA encoding flu virus nucleoprotein and liposome induced in vaccinated rodents anti-viral T cell responses [ 30 ]. Based on these data, nucleic acid immunization has received considerable scientific interest because of its significant advantages in comparison to conventional vaccines, i.e., ease of manufacturing, high stability, the capability of modifying genes encoding desired antigens, the ability to target cellular localization of an antigen by adding or removing signal sequences or transmembrane domains, and even the ability to elicit the type of immune response [ 31 , 32 , 33 , 34 ]. However, mRNA vaccine technology was halted for many years due to difficulties in manufacturing, the short half-life of mRNA, and its ability to activate the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In this pilot study, we developed the mRNA counterpart of our MultiTEP-based AV-1959D DNA vaccine using Vernal's proprietary vector for mRNA synthesis (Figure 1A). Specifically, the mRNA encodes the AV-1959 protein, which comprises three copies of the N-terminal region of human Aβ spanning amino acids 1-11, attached to an immunogenic vaccine platform, MultiTEP, consisting of twelve foreign promiscuous T helper (Th) cell epitopes, including one synthetic peptide (PADRE), eight epitopes from Tetanus Toxin (TT) (P2, P21, P23, P30, P32, P7, P17, and P28), two epitopes from HBV surface antigen (HBsAg, aa [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and the nucleocapsid (HBVnc, aa 50-69), respectively, and one epitope from influenza virus matrix protein (MT, aa [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The mRNA synthesis involved the incorporation of modified N1-methylPseudoUridine and capping (CAP1) at the 5 ′ end.…”
Section: Av-1959lr An Mrna-based Vaccine: the Counterpart Of The Av-1...mentioning
confidence: 99%